2002
DOI: 10.1088/0953-8984/14/33/309
|View full text |Cite
|
Sign up to set email alerts
|

Exotic fluids and crystals of soft polymeric colloids

Abstract: Abstract. We discuss recent developments and present new findings in the colloidal description of soft polymeric macromolecular aggregates. For various macromolecular architectures, such as linear chains, star polymers, dendrimers and polyelectrolyte stars, the effective interactions between suitably chosen coordinates are shown to be ultrasoft, i.e., they either remain finite or diverge very slowly at zero separation. As a consequence, the fluid phases have unusual characteristics, including anomalous pair co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 66 publications
5
94
0
1
Order By: Relevance
“…It has been shown that these systems may exhibit many different crystal structures, including rather exotic ones. [44][45][46][47] Therefore, the problem of finding the most stable structure for a certain thermodynamic state arises. Here, we have adopted a naive approach, consisting in performing many ( 30) runs for each state, corresponding to different minimization paths.…”
Section: B Minimization Methodsmentioning
confidence: 99%
“…It has been shown that these systems may exhibit many different crystal structures, including rather exotic ones. [44][45][46][47] Therefore, the problem of finding the most stable structure for a certain thermodynamic state arises. Here, we have adopted a naive approach, consisting in performing many ( 30) runs for each state, corresponding to different minimization paths.…”
Section: B Minimization Methodsmentioning
confidence: 99%
“…Two-length-scale potentials like we study are widely used 31,32,33,34,35,36,37,38,39,40,40 ; they qualitatively describe effective interactions in molecular systems, 41,42 soft matter systems 43,44,45,46,47 and metallic alloys 14,48,49,50,51 where QC formation has been experimentally observed but not completely accounted for.…”
Section: Introductionmentioning
confidence: 99%
“…Computer simulations have shown that spherical particles interacting isotropically through repulsive interparticle interactions on two different length scales ͑e.g., a square shoulder potential͒ can spontaneously assemble into anisotropic structures. [15][16][17] The presence of an isotropic short ranged interparticle attraction coupled to a longer ranged repulsion can also yield anisotropic structures. For instance, the assembly of spherical nanoparticles decorated with short alkanes into stripes on a substrate 18,19 or into nonequilibrium gels in three dimensions 20,21 can be rationalized on this basis.…”
Section: Introductionmentioning
confidence: 99%